Pathological Features of Enterovirus 71-Associated Brain and Lung Damage in Mice Based on Quantitative Proteomic Analysis - Jin, Yuefei; Li, Dong; Sun, Tiantian; Du, Yue; Gao, Yanlei; Ding, Ronghua; Ji, Wangquan; Zhang, Weiguo; Yang, Haiyan; Chen, Shuaiyin; Duan, Guangcai (Frontiers in Microbiology, 2021)
The outbreaks of enterovirus 71 (EV71)-associated hand, foot, and mouth disease (HFMD) have emerged as an emergency of global health due to its association with fatal encephalitis and subsequent neurogenic pulmonary edema; however, the molecular characteristics and pathological features underlying EV71-associated encephalitis and pulmonary edema remain largely unknown. In this study, we performed proteomic analysis of fresh brain and lung tissues from EV71-infected mice at 7 days post infection. We detected perturbed expression of 148 proteins in the brain and 78 proteins in the lung after EV71 expression. Further analysis showed that the dysregulated proteins in the brain are involved in a variety of fundamental biological pathways, including complement and coagulation cascades, innate and adaptive immune responses, platelet activation, and nitrogen metabolism, and those proteins in the lung participate in innate and adaptive immune responses, phagosome, Arginine biosynthesis, and hypoxia inducible factor 1 (HIF-1) signaling pathway. Our results suggested that immune activation, complement and coagulation dysfunction, platelet activation, the imbalance of nitrogen metabolism, and hypoxia could be involved in the pathogenesis of EV71, which explains the major clinical manifestation of hyperinflammatory status of severe HFMD cases. Our study provides further understanding of the molecular basis of EV71 pathogenesis.